Biodeteriogens at a southern Italian heritage site: Analysis and management of vascular flora on the walls of Villa Rufolo. (August 2021) - Motti, Riccardo; Bonanomi, Giuliano; Stinca, Adriano
Abstract: Colonisation of vascular plants on ancient historical buildings is known to cause severe damage. The aim of the present work was to analyse the deteriogenic vascular ﬂora of Villa Rufolo in Ravello, one of the most famous heritage sites in southern Italy. The deteriogenic flora were analysed in terms of diversity, structure, chorology, origin and potential damage to the building. The hazard index (HI) was applied to evaluate the impact of the biodeteriogens in question. The total flora included 61 taxa with the prevalence of therophytes (42.6%) and widely distributed species (42.6%), mostly derived from natural or semi-natural environments in the surrounding area (95.1%). The plant colonisation pattern showed the presence of some very harmful but not very abundant vascular plants (6.6%), including Ficus carica, Hedera helix subsp. helix, Capparis orientalis and Parthenocissus tricuspidata . Analysing the potential deteriogenic impact of each species (DI), a new index proposed by the authors, it emerged that the most dangerous were Centranthus ruber subsp. ruber and Parietaria judaica . Methods for the eradication of the most damaging species are discussed and proposed. Graphical abstract: Image 1 Highlights: The vascular plants colonising the monument Villa Rufolo are analysed. Hazard index and a new deteriogenic index proposed by authors are applied to evaluate the impact of the biodeteriogens. Therophytes and widely distributed species characterize the plant community. The surrounding natural vegetation is a reservoir of deteriogenic species. Italian endemic plants not very dangerous should not be uprooted.